2005
DOI: 10.1007/s10533-004-1717-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of dissolved carbon dioxide and inorganic carbon from an upland peat catchment: implications for soil respiration

Abstract: This study uses long-term water chemistry records for a circum-neutral peat stream to reconstruct a 7-year record of dissolved CO 2 and DIC flux from the catchment. Combining catchment flux with a knowledge of in-stream metabolism and gas evasion from the stream surface enables an estimate of the dissolved CO 2 content of water emerging from the peat profile to be made; furthermore, these can be used to estimate soil CO 2 respiration. In this way multi-annual records of CO 2 production can be reconstructed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…Ditchwater and soil water were therefore barely fed with TC and CH 4 through seepaging water. Discharge in this controlled area was low compared to other, for example mountainous and uncontrolled areas, where the run off component forms a more important role of washing down of carbon from the system (Hope et al, 2004;Worrall et al, 2005;Ding et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…Ditchwater and soil water were therefore barely fed with TC and CH 4 through seepaging water. Discharge in this controlled area was low compared to other, for example mountainous and uncontrolled areas, where the run off component forms a more important role of washing down of carbon from the system (Hope et al, 2004;Worrall et al, 2005;Ding et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…There are no calcium concentration data available here; however, Worrall and Burt (2005a) have shown that a strong linear correlation exists between EpCO 2 as calculated based upon pH, alkalinity and stream temperature alone and that calculated using calcium concentration data. This strong linear correlation has been observed in three different catchments (Worrall et al, 2005) Dissolved CO 2 is converted to units of milligrams of carbon per litre.…”
Section: Estimating Stream Dissolved Comentioning
confidence: 79%
“…Worrall et al (2005) have shown that the approach of Jones and Mulholland (1998) gives comparable results to those of extrapolation from soil temperature within a peat soil catchment. This present study calculates the excess dissolved CO 2 concentration at emergence as described below.…”
Section: Surface Exchange Of Comentioning
confidence: 81%
“…The rating curve for the Trout Beck gauging station was used to estimate stream depth and, given the total stream length within the catchment it was assumed that the CO 2 evaded the stream at the mid-length point. The in-stream production was estimated following the method of Worrall et al (2005) based upon measurements of biochemical oxygen demand (BOD) across a range of low conditions within the catchment.…”
Section: Dissolved Comentioning
confidence: 99%